Life Skill-Based Education on Entrepreneurship Using Business Model Canvas in Vocational School - Bahrul Ulum; Frendy Aru Fantiro; Mohammad Novi Rifa'i (IJER (Indonesian Journal of Educational Research), 2019)
The entrepreneurship-based life skill education program for students continues to be improved andendeavored to be better learning than the previous one. The Purpose of this study was to describe lifeskills education based on entrepreneurship using a business model canvas at Vocational High School.The research used descriptive qualitative and using recorded technical literature study. Life skillseducation can be seen from entrepreneurship learning of Vocational high school students. One of them isusing a business model canvas which is a business planning tool that is presented in a visual form on onecanvas to explain, visualize, assess, and change an effort so that it can produce more optimalperformance.